Increased Activity of “Anti-Willebrand Factor” in Diabetic Plasma - Ödegaard, A. E; Skalhegg, B. A; Hellem, A. J (Thrombosis and Haemostasis, 1964)
In a group of 25 patients with insulin-treated diabetes mellitus a marked increase in the ADP-induced platelet adhesiveness was demonstrated. This phenomenon was due to a plasmatic factor. In vitro-plasma from these patients restored the decreased ADP-induced platelet adhesiveness in von Willebrand’s disease.The factor was also effective in vivo, since transfusion of 450 ml diabetic plasma to a patient with von Willebrand’s disease normalized the decreased platelet adhesiveness and shortened the prolonged bleeding time. The role of this factor in the ADP platelet reaction as a cofactor together with calcium is stressed.